Identifying and Developing Measures of Information Technology Ethical Work Climates - Stone, Robert W. (Journal of business ethics, 2003)
A model of information technology (IT) ethical work climates is presented. Using these ethical work climates and data collected from a national mail survey of Association for Computing Machinery (ACM) members, empirical measures were developed and evaluated. A mailing of 2446 questionnaires was sent to ACM members and 136 usable responses were returned (5.6%). Using these data, an exploratory factor analysis was performed using principle components analysis to identify the IT ethical work climates from the data. Six of these work climates were identified as predicted by the model. Two ethical work climates that were combinations of the proposed climates were also identified., From the results of the exploratory factor analysis, a confirmatory factor analysis was performed using Calis in PC SAS version 8. The purpose of this analysis was to evaluate the overall fit of these measures to the data and evaluate the psychometric properties of the measures. The fit of the IT ethical work climates model was acceptable. The psychometric properties of these measures were good. Based on these results, conclusions, limitations of the study, and directions for future research are proposed.